Studi Perilaku Menyimpang : Faktor Penyebab Pembunuhan Berlatar Belakang Asmara di Lapas Cipinang (International Forum of Researchers and Lecturers, 2025)
This study examines murder cases triggered by romantic conflicts in Cipinang Prison, Jakarta. Using a qualitative approach, this research employed in-depth interviews with inmates and prison officers to explore the motives, processes, and social and psychological perspectives of the perpetrators. The findings reveal that romantic conflicts, such as jealousy, financial pressures, and feelings of being undervalued, are often the main triggers of violent acts leading to murder. Uncontrolled emotions and impulsive reactions exacerbate the situation, while the social environment, both before and during incarceration, plays a significant role in shaping deviant behavior patterns. The study also identifies various challenges in the rehabilitation process within the prison, including insufficient attention to the emotional needs of inmates and the negative influence of interactions with fellow prisoners. Referring to Differential Association theory, the study emphasizes that deviant behavior is often learned through negative social interactions. To prevent similar violence, emotional education, conflict management, and evaluations of individual-based rehabilitation programs are necessary.